Industrial Innovation, Labour Productivity, Sales and Employment. Issue 1 (2nd January 2021) - Woltjer, Geert; van Galen, Michiel; Logatcheva, Katja
Abstract: This article examines the relationship between firm-level innovation and employment growth for industrial firms in the Netherlands. The empirical analysis uses four waves of the CIS survey for the period 2002-2010. It extends the literature by making an explicit split between the expansion effect of innovation and the labour productivity effect. The results show that both product and process innovation increase labour productivity and therefore induce direct reductions in employment. However, these negative employment effects are more than compensated by increases in sales, implying that both process and product innovations increase employment. In this article for the first time the relationship between both product and process innovations and employment is decomposed in a systematic manner based on explicit econometric equations on the relationship between innovation and labour productivity respectively sales. It is argued that the effects for sales and labour productivity are probably underestimated in all research that uses CIS survey data because these do not show the price effects of increased productivity, but that this effect cancels out in the estimated employment equation.